Effect of different light spectra on the pigmentation of stored elephant garlic. (11th December 2017) - Comparini, Diego; Nguyen, Hieu TH; Ueda, Kota; Moritaka, Kyoshi; Kihara, Toshihiko; Kawano, Tomonori
Abstract: BACKGROUND: In the present study high‐brightness light‐emitting diodes were used to investigate the influence of different light spectra on garlic discoloration at different humidity levels and temperature. Many processes involved in the discoloration process of garlic/leek during storage under different conditions remain unanswered. For this reason in this study the ability of specific light spectra to enhance the production of desirable pigments has been evaluated in elephant garlic. It is well known that the pigments involved in the discoloration reaction are of great interest because of their potential ability to increase the nutritional value and health benefits of the food. RESULTS: In the present study, we show how the chlorophyll content of the sprout increases directly proportionally to the wavelength of the light tested; green/blue light delays the greening process of garlic young shoots whilst red/infra‐red light irradiance conditions increase the greening process at different storage temperatures and humidity. Moreover different lights in the visible spectrum have been observed to stimulate and enhance the outer layer purple coloration. CONCLUSION: The use of different lights to modulate garlic pigmentation has been demonstrated and, in particular, the utilisation of red/green/blue lights and lower temperature resulted in higher red/pink pigments production supporting the hypothesis that this process involves more than one light to be fully performed and the low temperature is a condition that influences the formation of these products. © 2017 Society of Chemical Industry